Peningkatan Kualitas Perangkat Desa Guna Pemantapan Pelaksanaan Pembangunan di Desa Ilotidea Kabupaten Gorontalo - Sahi, Nirmala (Gorontalo Journal of Public Administration Studies, 2018)
This study aims to determine the improvement of the quality of village apparatus in order to strengthen the implementation of development in Ilotidea Village, Tilango District, Gorontalo Regency. The research method used qualitative descriptive method. Data obtained through interviews, observation and documentation. The sample used in this study were 25 respondents from the total population of 50 respondents. The results of the research show several findings are: First, the quality of village apparatus is still not optimal or still very need to be improved. Secondly, the ability, willingness and potential of the village apparatus and the impacts and approaches of governance and the implementation of development have not been maximized because human resources are still limited.